2015
DOI: 10.1002/pon.3751
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with emotional distress in newly diagnosed prostate cancer patients

Abstract: Objective-Early identification and intervention have been recommended for newly diagnosed prostate cancer patients who experience significant emotional distress; however, there is little empirical basis for designing or selecting interventions for these men. We sought to identify factors that are associated with distress in these men as a basis for identifying suitable intervention strategies.Methods-Using cross-sectional data and validated scales, we investigated the extent to which clinical, demographic, bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 39 publications
6
51
1
Order By: Relevance
“…After adjusting for several previously identified confounding variables, the findings show a moderating effect of race on the relationship between cancer history and emotional distress, with African American cancer long-term survivors experiencing significantly higher levels of emotional distress compared to the general cancer and non-cancer populations. Consistent with previous studies, the study also found associations between socio-demographic factors [7], physical health [20], self-efficacy [11,21], optimal lifestyle behaviors [22][23][24], and emotional distress.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…After adjusting for several previously identified confounding variables, the findings show a moderating effect of race on the relationship between cancer history and emotional distress, with African American cancer long-term survivors experiencing significantly higher levels of emotional distress compared to the general cancer and non-cancer populations. Consistent with previous studies, the study also found associations between socio-demographic factors [7], physical health [20], self-efficacy [11,21], optimal lifestyle behaviors [22][23][24], and emotional distress.…”
Section: Discussionsupporting
confidence: 89%
“…However, compared to the matched Caucasian control group, a lower proportion of African American patients in this study reported depressive symptoms. In contrast, Orom et al [11] observed a marginally significant (p = 0.05) positive association between African American race and emotional distress among newly diagnosed prostate cancer patients.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Distress was slightly lower after men had made their treatment decision, but it remained a predictor of having chosen surgery over active surveillance and surgery over radiation in the sample as a whole and in men with low risk disease. A number of studies have shown that emotional distress is relatively high among newly diagnosed men, 12,16,24 but our study is novel as it demonstrates both prospectively and cross-sectionally that emotional distress motivates PCa patients to choose more aggressive treatment.…”
Section: Discussionmentioning
confidence: 79%
“…study of PCa treatment decision making and survivorship. 16 Participants with newly diagnosed clinically localized PCa were approached at two comprehensive cancer centers and three community facilities between July 2010 and August 2014. Of the 3337 patients approached to participate, 2,476 were consented; 2,008 completed the first survey.…”
Section: Methodsmentioning
confidence: 99%